A vision based feedback mechanism for 6-DOF Stewart Platform - Buyuksahin, Utku (Tubitak Scientific & Technological Research Council Turkey, 2011)
Eyes are the most ubiquitous sensors of humankind. However, Vision Based Sensors are not as common as what this fact would suggest. A survey of the previous work on image processing would reveal that the bulk of the research in this area, have been. conducted since the year 2000. These facts clearly show that image processing is the technology of our century, and is very open to further development. In this work, a system that combines a classical mechanism of the 20th. century with the recent technology of the 21st century is presented and the design, theoretical background, the software algorithm for a vision based, low cost feedback mechanism is given. Simulation results based on the image processing of a 3-D animated model of a Stewart Platform through the aforementioned feedback system are also included. These results demonstrate that the software performed all necessary tasks to compute the leg lengths successfully.
Keywords: Stewart Platform; image recognition; feedback mechanism; Computer Science; Engineering